2016
DOI: 10.1097/md.0000000000003328
|View full text |Cite
|
Sign up to set email alerts
|

Use of Wisteria Floribunda Agglutinin-Positive Human Mac-2 Binding Protein in Assessing Risk of Hepatocellular Carcinoma Due to Hepatitis B Virus

Abstract: Wisteria floribunda agglutinin-positive human Mac-2 binding protein (WFA+-M2BP) is a serologic marker corresponding with degree of hepatic fibrosis. We evaluated its accuracy in assessing hepatic fibrosis and in predicting the risk of developing hepatocellular carcinoma (HCC) in patients with chronic hepatitis B (CHB).In a 5-year period (2009–2013), a total of 95 CHB patients with available serum WFA+-M2BP assay and transient elastography assessment [to assess liver stiffness (LS)] who had undergone liver biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…Based on these studies, a higher WFA + ‐M2BP value was significantly correlated with a higher rate of HCC development. In the study by Heo et al , all patients were HBV positive, and 78/95 (82%) received antiviral therapy. The HR in HBV patients was quite high compared with those in other patients.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on these studies, a higher WFA + ‐M2BP value was significantly correlated with a higher rate of HCC development. In the study by Heo et al , all patients were HBV positive, and 78/95 (82%) received antiviral therapy. The HR in HBV patients was quite high compared with those in other patients.…”
Section: Resultsmentioning
confidence: 98%
“…We identified four studies that reported the development of HCC and HRs for higher WFA + ‐M2BP levels (Table ). Based on these studies, a higher WFA + ‐M2BP value was significantly correlated with a higher rate of HCC development.…”
Section: Resultsmentioning
confidence: 99%
“…We then divided this study population into subgroups of patients with or without cirrhosis to determine the prognostic performance of WFA + ‐M2BP level in these two subgroups using a cutoff value of 1.8, which identified low‐ and high‐risk patients in our previous study . In the subgroup without cirrhosis (n=1,087), patients with high WFA + ‐M2BP levels (≥1.8) showed significantly greater risk of developing HCC than those with low WFA + ‐M2BP levels (<1.8) ( P <.001 by log‐rank test) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies show that WFA + ‐M2BP has high cross‐sectional diagnostic accuracy and good prognostic performance for chronic liver diseases such as chronic hepatitis C, primary biliary cirrhosis, and non‐alcoholic fatty liver disease . In particular, our group described the cross‐sectional diagnostic performance and longitudinal prognostic performance of WFA + ‐M2BP in predicting HCC development in CHB patients . However, the overall sample size and the number of patients who developed HCC was too small to draw a solid conclusion.…”
Section: Introductionmentioning
confidence: 95%
“…However, LB is often limited by its invasiveness and extremely rare, but fatal complications including procedure-related mortality, high cost, low patient acceptance, reluctance of physicians, need for expertise, prolonged procedure time, interobserver/intraobserver interpretational variability, sampling error, and poor reproducibility 4. Accordingly, various biochemical surrogates for LB, such as the FibroTest, enhanced liver fibrosis test and Wisteria floribunda agglutinin-positive human Mac-2 binding protein (M2BP),5,6 as well as physical surrogates such as transient elastography (TE) and acoustic radiation force impulse elastography, have been proposed to noninvasively assess the fibrotic burden in patients with CLDs 2. Most recently, advances in magnetic resonance imaging (MRI) have enabled assessment of the degree of liver fibrosis, irrespective of etiology 7,8…”
mentioning
confidence: 99%